(untitled) (Journal of Biomedical Investigation, 2025)
Background: Axillary crutches are commonly prescribed for patients with lower limb fractures to facilitate protected ambulation. Although crutch-assisted gait increases acute metabolic and cardiovascular demand, its longitudinal physiological effects remain unclear. This study investigated whether a six-week supervised axillary crutch walking program would produce measurable changes in selected physiological parameters compared with usual care. Methods: A randomized pretest–posttest-controlled trial was conducted at the National Orthopaedic Hospital, Enugu, Nigeria. Forty-five patients with lower limb fractures (22 males, 23 females) prescribed axillary crutches were randomized to an experimental group (n = 29), which received supervised crutch walking training three times weekly for six weeks, or a control group (n = 16), which received usual physiotherapy care. Outcome measures included resting systolic and diastolic blood pressure, resting heart rate, estimated VO₂max (derived from resting heart rate), and percentage body fat measured via bioelectrical impedance. Analysis of covariance (ANCOVA) was used to compare post-intervention outcomes while adjusting for baseline values (p < 0.05). Results: No statistically significant between-group differences were observed after six weeks. Resting systolic blood pressure (F = 0.363, p = 0.64), diastolic blood pressure (F = 2.153, p = 0.15), resting heart rate (F = 0.96, p = 0.758), estimated VO₂max (F = 0.2, p = 0.65), and percentage body fat (F = 0.4, p = 0.5) showed no significant group effects. Conclusion: The six-week supervised axillary crutch walking program did not produce significant cardiovascular or body composition adaptations beyond usual physiotherapy care in patients with lower limb fractures.